Closed glabellar myotomy: a new surgical approach to treat wrinkles without scarring - Rogerio Schutzler Gomes; Daniel Ongaratto Barazzetti; Guilherme Pintarelli (Revista Brasileira de Cirurgia Plástica, 2018)
INTRODUCTION: Hyperactivity of the glabellar musculature and resulting wrinkles are frequent complaints in the field of plastic surgery. Treatment consists of blocking the involved muscles. We propose a closed approach for the treatment of glabellar musculature. METHODS: Seventy-eight patients underwent operation between April 2012 and August 2015. Myotomy includes the use of markings and polyglactin 0 wire or steel wire, passing through the marked lines several times, entering the eyebrow and using the juxtaperiostal plane, returning through the same orifice of the needle toward the entry hole, and using the subcutaneous plane. RESULTS: Good results were obtained in all cases by preventing glabellar muscle activity during the period evaluated (at least 1 year), with improvement in wrinkles and muscle hyperactivity. The complications observed included temporary paresthesia in the frontal region (35 cases) and partial recurrence (4 cases). There was no case of total recurrence. The options for long-term surgical treatment of glabellar wrinkles are myotomy, partial neurotomy, or myectomy. Closed glabellar myotomy prevents some possible complications associated with these options, reduces the surgical time, requires the use of conventional surgical instruments, eliminates scarring, and causes asymmetric correction, less edema, and fewer bruises. CONCLUSION: Closed glabellar myotomy seems to be a good alternative compared to other traditional surgical options, because it eliminates scarring, allows correction of asymmetry, and presents good long-term results.